Differential resistive transducer for power harvesting for implanted devices - Khan, Sheroz; Habul, Emir; Khalifa, Othman Omran; Alam, A. H. M. Zahirul (2010)
This work is aimed at powering implanted electronic device with sensors meant for collection of biomedical signals. This is done through inductive coupling technique employed not only to transfer power (mW level) but also to make data available to the external world for monitoring purposes. It is primarily an analysis associated with transferring digital signal in order to power implanted electronics for signal acquisition. Hence, this work is aimed to provide both a power as well a signal link between the external world and the implanted electronic devices.